Does physical protection of soil organic matter attenuate temperature sensitivity? - Conant, Richard T., author; Paul, Eldor A., author; Six, Johan, author; Plante, Alain F., author; Soil Science Society of America, publisher (Colorado State University. Libraries, 2009)
Global climate change may induce accelerated soil organic matter (SOM) decomposition through increased soil temperature, and thus impact the C balance in soils. We hypothesized that compartmentalization of substrates and decomposers in the soil matrix would decrease SOM sensitivity to temperature. We tested our hypothesis with three short-term laboratory incubations with differing physical protection treatments conducted at different temperatures. Overall, CO2 efflux increased with temperature, but responses among physical protection treatments were not consistently different. Similar respiration quotient (Q 10) values across physical protection treatments did not support our original hypothesis that the largest Q 10 values would be observed in the treatment with the least physical protection. Compartmentalization of substrates and decomposers is known to reduce the decomposability of otherwise labile material, but the hypothesized attenuation of temperature sensitivity was not detected, and thus the sensitivity is probably driven by the thermodynamics of biochemical reactions as expressed by Arrhenius-type equations.
Keywords: decomposition; CO2 respiration; global C cycle; SOM